2001
DOI: 10.1177/0022002701045004005
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Violence, and International Crisis

Abstract: Women work for peace, and men wage war—cooperative women, conflictual men. These images pervade conventional wisdom about the efficacy of women in leadership roles and decision-making environments, but imagery is not always grounded in reality. Feminist international relations literature is examined to understand how domestic gender equality may help predict a state's international crisis behavior. The authors use the record of female leaders as primary decision makers during international crises and then test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
168
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(172 citation statements)
references
References 29 publications
0
168
2
2
Order By: Relevance
“…"Female leaders who have risen to power through a male-defined and male dominated political environment may well need to be more aggressive in crises than their male counterparts… women may also work harder to 'win'… because to appear and act feminine (and therefore weak) would be political suicide" [32] In other words, a woman leader must exhibit masculine (aggressive, rational) traits in order to be taken seriously; however, we often expect women leaders to be both feminine (caring, nurturing, soft) and masculine at the same time. [33] Women leaders are faced with a political double bind.…”
Section: Gender Preferences and Stereotypesmentioning
confidence: 99%
“…"Female leaders who have risen to power through a male-defined and male dominated political environment may well need to be more aggressive in crises than their male counterparts… women may also work harder to 'win'… because to appear and act feminine (and therefore weak) would be political suicide" [32] In other words, a woman leader must exhibit masculine (aggressive, rational) traits in order to be taken seriously; however, we often expect women leaders to be both feminine (caring, nurturing, soft) and masculine at the same time. [33] Women leaders are faced with a political double bind.…”
Section: Gender Preferences and Stereotypesmentioning
confidence: 99%
“…Governments with more women in legislature are less likely to use military force, 70 and spend less on the military 71 and more on development assistance 72 than governments with fewer women. Countries with more women in government are also less likely to abuse human rights within the country.…”
Section: More Women's Engagementmentioning
confidence: 99%
“…Both refer to institutionalised forms of social, cultural and political dominance which work to systematically oppress those groups who find themselves powerless in the face of both patriarchal and economic domination. A good example of the kind of evidence suggesting that such linkages are causal comes from the field of international relations (Caprioli and Boyer, 2001). A worldwide study linking levels of female representation in national parliaments and duration of female suffrage with governmental use of political violence found that 'States that are characterized by higher levels of gender equality use lower levels of violence during international crises than those with lower levels of gender equality'.…”
Section: Structural Violencementioning
confidence: 99%